Detection Limits for In-Situ Identification of Damaged Blades - Boström, Alexander (My University, 2025)
Over the past decade, axial turbomachinery has seen substantial technological advancements, particularly in improving efficiency and reducing operational costs in aviation. This study investigates the in-situ automatic detection of damage and wear of compressor blades, aiding the enhancement of operational efficiency, reliability, and safety throughout the component lifecycle. The primary objective is to assess the aerodynamic impact of leading-edge erosion on a compressor rotor blade and to determine the detectability limits of such erosion using existing instrumentation in a dedicated experimental test rig. A series of tests with increasing erosion severity was numerical investigated under both subsonic and transonic flow conditions. Reynolds-Averaged Navier–Stokes (RANS) simulations were performed at multiple operating points at design speed for an experimental rotor blisk , comprising 18 blades. Key flow parameters, including static pressure coefficient, Mach number, and entropy contours, were analyzed to qualitatively and quantitatively evaluate the flow physics. All test cases exhibited a reduction in polytropic efficiency, with the most significant drop—2.17 percentage points—observed near stall under transonic conditions. Flow field alterations due to erosion included increased profile losses, enhanced tipleakage effects, and changes in shock structures in transonic regimes. The current sensor configuration in the experimental rig is expected to detect all investigated erosion severities within ±0.2 axial chord lengths around the rotor leading edge under transonic conditions.
Keywords: Axial turbomachinery; Compressor blades; Leading-edge erosion; In-situ damage detection; Aerodynamic performance; Sensor detectability limits